OPTIMIZED PLANNING OF ASSORTMENT PRODUCTION IN FOREST STANDS - Fiorentin, Luan Demarco; Arce, Julio Eduardo; Pelissari, Allan Libanio; Miranda, Rodrigo Otávio Veiga de; Freitas, Thaís Wisniewski de (Floresta, 2019)
This study aimed to evaluated two optimized planning strategies and analyze their performance in timber production. Data were obtained in Pinus spp. stands from a forestry company with unbalanced planted area over time. Maximization models of forest production (1) and net present value (2) were formulated and two minimization objective functions of the production deviation (3) and minimum and maximum production oscillation (4) were tested as alternatives to the traditional models. The highest thinning and clearcutting average areas were obtained in strategy 1. Strategies 1 and 2 resulted in the greatest variability of forestry operations. All strategies resulted in the highest timber production for sawn and special sawn wood and the lowest for veneer, while the pulpwood volume was almost constant. Strategies 1 and 2 provided the highest average timber volume and the greatest variability in the production, while strategies 3 and 4 were more efficient, since they supplied the industrial demand with homogeneous production.